Anatomical changes in descending serotonergic projections from the rostral ventromedial medulla to the spinal dorsal horn following repetitive neonatal painful procedures. Issue 4 (12th April 2022) - de Kort, Anne R.; Joosten, Elbert A.; Versantvoort, Eline M.; Patijn, Jacob; Tibboel, Dick; van den Hoogen, Nynke J.
Abstract: Excessive noxious stimulation during the critical neonatal period impacts the nociceptive network lasting into adulthood. As descending serotonergic projections from the rostral ventromedial medulla (RVM) to the spinal dorsal horn develop postnatally, this study aims to investigate the long‐term effect of repetitive neonatal procedural pain on the descending serotonergic RVM–spinal dorsal horn network. A well‐established rat model of repetitive noxious procedures is used in which neonatal rats received four noxious needle pricks or tactile stimulation with a cotton swab per day in the left hind paw from day of birth to postnatal Day 7. Control animals were left undisturbed. When animals reached adulthood, tissue was collected for quantitative immunohistochemical analysis of serotonin (5‐hydroxytryptamine, 5‐HT) in the RVM and spinal dorsal horn. Both repetitive noxious and tactile procedures in the neonate decreased the 5‐HT staining intensity in the adult ipsilateral but not contralateral spinal dorsal horn. Repetitive neonatal noxious procedures resulted in an increased area covered with 5‐HT staining in the adult RVM ipsilateral to the side of injury, whereas repetitive neonatal tactile stimulation resulted in increased 5‐HT staining intensity in both the ipsi‐ and contralateral RVM. The number of 5‐HT cells in adult RVM is unaffected by neonatal conditions. This detailed anatomical study shows that not only neonatal noxious procedures but also repetitive tactile procedures result in long‐lasting anatomical changes of the descending serotonergic system within the RVM and spinal dorsal horn. Future studies should investigate whether these anatomical changes translate to functional differences in descending serotonergic modulation after neonatal adverse experiences.